Hadits Shahih, Hasan, Dan Dhaif Dalam Perspektif Hukum Islam: Sebuah Perbandingan Kualitatif - Ahmad Thoyib Masudi (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2023)
Hadith, which is the second source of law after the Quran, plays an important role in elucidating the verses of the Quran. To understand hadith-based law, it is important to evaluate the authenticity of the hadith. This study is a review of the literature and falls under the category of qualitative research. The purpose of this study is to analyze the authenticity of hadith, which can be classified into three groups: Sahih, Hasan, and Daif. The authenticity of hadith varies, with sahih hadith being the strongest, followed by hasan hadith, and the weakest being daif hadith.